An absurd way of life: `A very unusual feeling'. - Prochazka, Marta (Canadian Ethnic Studies, 1993)
Presents an excerpt of Czech refugee Marta Prochazka's 1992 series of articles from the `Grizzly Gazette of Swan Hills, Alberta on her family's migration to Swan Hills.